2021
DOI: 10.1007/s00418-021-01962-5
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-activated chloride channel-associated protein rCLCA2 is expressed throughout rat epidermis, facilitates apoptosis and is downmodulated by UVB

Abstract: The rodent chloride channel regulatory proteins mCLCA2 and its porcine and human homologues pCLCA2 and hCLCA2 are expressed in keratinocytes but their localization and significance in the epidermis have remained elusive. hCLCA2 regulates cancer cell migration, invasion and apoptosis, and its loss predicts poor prognosis in many tumors. Here, we studied the influences of epidermal maturation and UV-irradiation (UVR) on rCLCA2 (previous rCLCA5) expression in cultured rat epidermal keratinocytes (REK) and correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Concordantly with the high degree of conservation, maCLCA2 is consistently expressed in keratinocytes of stratified epithelia such as those of skin or esophagus and in certain glandular epithelia in all mammals investigated so far ( Braun et al, 2010 ; Connon et al, 2006 ; Connon et al, 2004 ; Erickson, Gruber & Mundhenk, 2020 ; Hamalainen et al, 2021 ; Plog et al, 2012b ; Seltmann et al, 2018 ; Walia et al, 2012 ). It has been proposed that the CLCA2 protein is involved in epithelial differentiation, growth arrest and maturation of keratinocytes ( Connon et al, 2004 ; Koegel & Alzheimer, 2001 ; Ramena et al, 2016 ).…”
Section: Introductionmentioning
confidence: 54%
“…Concordantly with the high degree of conservation, maCLCA2 is consistently expressed in keratinocytes of stratified epithelia such as those of skin or esophagus and in certain glandular epithelia in all mammals investigated so far ( Braun et al, 2010 ; Connon et al, 2006 ; Connon et al, 2004 ; Erickson, Gruber & Mundhenk, 2020 ; Hamalainen et al, 2021 ; Plog et al, 2012b ; Seltmann et al, 2018 ; Walia et al, 2012 ). It has been proposed that the CLCA2 protein is involved in epithelial differentiation, growth arrest and maturation of keratinocytes ( Connon et al, 2004 ; Koegel & Alzheimer, 2001 ; Ramena et al, 2016 ).…”
Section: Introductionmentioning
confidence: 54%
“…As a new calcium activated chloride channel protein, CLCA2 plays an important role in tumorigenesis and development. Most studies have shown that there are abnormal expression levels and related signaling pathways of CLCA2 in malignant tumors, and it is closely related to tumor invasion and metastasis [ 7 , 23 , 24 ], CLCA2 is down regulated in cervical cancer [ 25 , 26 ], but its role and exact regulatory mechanism in cervical cancer are still unclear. Our results confirmed that the expression of CLCA2 was significantly decreased in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, distinct functional species-related differences among the various chloride channel accessory proteins have been reported. Therefore, Hämäläinen et al (2021) have analyzed the expression and possible function of the rat calcium-activated chloride channel-associated protein rCLCA2 in cultured rat epidermal keratinocytes and correlated their findings with the mouse homolog in mouse skin (Fig. 4).…”
Section: A Chloride Channel-associated Protein Keeps Keratinocytes Quietmentioning
confidence: 99%